General Social Function for Elderly in Geriatric Homes in Jordan - Nazar A. Sherin (Iraqi National Journal of Nursing Specialties, 2023)
Objectives: To assess general social factors for elderly in geriatric homes in Jordan. Methodology: The study was conducted for clients residing in elderly homes. A purposive sample of (155) residents were selected. Social resource scale by (Duck University Center) called (OARA) older adult resources and services was used as tool for data collection. The questions extract data about family structure, patterns of friends and visiting, availability of a confident, satisfaction with the degree of social interaction and availability of a helper in the event of illness or disability and the program of trips in the houses. Results: The findings revealed that the life expectancy for women is greater than for men. In respect to marital status, the majority of the residents were widows who represented (38.I). Only ( 15.5%) of them were visited by their family more than (5) tines in the year. The study shows that (61.3%) of them have trust to the home’s staff and (25.1%) to their friends in the home. In regard to loneliness, (66.5%) of them feels loneliness and they need outside assistance, In regard to clients’ help, (42%) of them could not know or answer this question. While, (51.6%) of them need help from inside on bathing, eating or taking medication. In relation to clients trips outside home, (54.8%) of them have the chance to go outside the home for trip; mainly for visiting family, friends or for religious purposes. Recommendation: The study recommended that the leaders of the homes must focus on increasing the facilities of social relation through more communication, increase visiting times between the elderly and their families through the social worker of the house, get out of the house and meet other people, invite people home, an.ange regular tines for getting together with fiiends and family members, and find activities that involve doing things.